The impact of enterprise resilience and HRM practices on performance: Findings from fsQCA - Bo Liu; Yan Li; LinHua Tang; Yipeng Zhao; Haodong Chang (Frontiers in Psychology, 2023)
BackgroundBoth enterprise resilience and HRM practices can have a positive impact on enterprise performance. The impact of enterprise resilience or human resource management (HRM) practices on enterprise performance independently has been studied widely. But few studies have combined the above two aspects to discuss their impact on enterprise performance.ObjectiveIn order to provide positive conclusions for improving enterprise performance, the theoretical model is established to expound the relationship between enterprise resilience, HRM practices including their internal influencing factors and enterprise performance. According to this model, a series of hypotheses about the influence of the combination from these internal factors on enterprise performance are presented.MethodBased on the statistical data of the questionnaire survey with managers and general employees at different levels in enterprises as respondents, the correctness of these hypotheses is proved by the fuzzy set qualitative comparative analysis (fsQCA) method.Results and discussionThe impact of the combination of enterprise resilience for high enterprise performance is shown in Table 3. The positive impact on the configuration of HRM practices for enterprise performance is shown in Table 4. The influences of the various combinations of internal factors about enterprise resilience and HRM practices on enterprise performance are shown in Table 5. From Table 4, it is discovered that performance appraisal and training have a significant positive effect on high enterprise performance. From Table 5, it is found that information sharing capabilities play a critical role, and enterprise resilience capabilities have a relatively positive impact on enterprise performance. Therefore, managers need to seek the development of enterprise resilience and HRM practices simultaneously and choose the most suitable combination configuration according to the actual situation of the enterprise itself. Moreover, a meeting system should be set up to ensure the transmission of internal information efficiently and accurately.